2022
DOI: 10.1097/ftd.0000000000000924
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Drug Interactions With Over-The-Counter Medicines: Mind the Unprescribed

Abstract: Background:This review provides a summary of the currently available clinical data on drug–drug interactions (DDIs) involving over-the-counter (OTC) medicines. It aims to educate and increase awareness among health care providers and to support decisions in daily practice.Methods:An extensive literature search was performed using bibliographic databases available through PubMed.gov. An initial structured search was performed using the keywords “drug-drug-interaction AND (over-the-counter OR OTC),” without furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 215 publications
0
12
0
Order By: Relevance
“…We have shown, that only 4% antidepressant drug interactions were related to OTC medication. This low detection rate is most likely associated with lack of awareness, rather than rare occurrence of those interactions, what has been also pointed out in the case of studies evaluating prevalence of such drug interactions (Hämmerlein et al, 2007;Scherf-Clavel, 2022). Nationwide survey in Germany showed that only 8.6% of drug-related problems were associated with the use of OTC drugs (Hämmerlein et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…We have shown, that only 4% antidepressant drug interactions were related to OTC medication. This low detection rate is most likely associated with lack of awareness, rather than rare occurrence of those interactions, what has been also pointed out in the case of studies evaluating prevalence of such drug interactions (Hämmerlein et al, 2007;Scherf-Clavel, 2022). Nationwide survey in Germany showed that only 8.6% of drug-related problems were associated with the use of OTC drugs (Hämmerlein et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…In this Frontiers in Pharmacology frontiersin.org effort, the physicians should not only pay attention to the medications they prescribed, but should also place these in a critical context with the medications prescribed by physicians from other specialties. When checking for pDDIs, the use of OTC drugs should not be neglected (Scherf-Clavel, 2022) as, according to our previous study, about one in five pDDIs is related to OTC medicines in patients with MS (Bachmann et al, 2022). If a clinically relevant pDDI is identified, there are various options for dealing with it.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that many patients take OTC drugs, and analgesics are the most common ones. These are highly potent drugs which are also commonly prescribed and can cause DRPs such as side effects and drug interactions [ 29 , 30 ]. OTC drugs will not be included in the National shared medication list in the beginning, but this should be considered in the future along with medications administered in the hospitals.…”
Section: Discussionmentioning
confidence: 99%